2011
DOI: 10.2147/oajc.s9674
|View full text |Cite
|
Sign up to set email alerts
|

Users’ perspectives on Implanon in Malaysia, a multicultural Asian country

Abstract: Background:The primary objective of this study was to evaluate Malaysian women's perception, acceptance, and views on Implanon ® as a contraceptive method. We also aimed to identify women who favor Implanon, their vaginal bleeding patterns, nonmenstrual adverse events, reasons for discontinuation, and effect of Implanon on breastfeeding. Study design: This study followed up 140 women after insertion of Implanon at the University of Malaya Medical Centre by examination of their medical records and telephone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 18 publications
6
15
6
Order By: Relevance
“…This rate is consistent with the study conducted in Australia where 47% [17]of women using the implant discontinued within three years. However, it is higher than the study conducted in Nigeria, Egypt and Malaysia where the overall Implanon discontinuation rateswere 26.1%, 28% and 22.86% respectively [7,18,19]. Similarly, the rates of discontinuation at 6months, 12 months and 24 months were 10.5%, 23.9% and 38.2% which is higher than discontinuation rate observed in the above studies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This rate is consistent with the study conducted in Australia where 47% [17]of women using the implant discontinued within three years. However, it is higher than the study conducted in Nigeria, Egypt and Malaysia where the overall Implanon discontinuation rateswere 26.1%, 28% and 22.86% respectively [7,18,19]. Similarly, the rates of discontinuation at 6months, 12 months and 24 months were 10.5%, 23.9% and 38.2% which is higher than discontinuation rate observed in the above studies.…”
Section: Discussionmentioning
confidence: 58%
“…Studies conducted in Ofla district of Tigray region and Arsi zone of Oromia region, Ethiopia, were carried outin rural areas and majority of the participants (70%) have no formal education, and the remaining30 % were primary and secondary school [16,29]. On the other hand, studies conducted in Nigeria, Malaysia, America and Australia indicatedthat themajority of the participants (66%) were college and above while only a few of them were illiterate [6,7,18,27]. However, the participants of this study have differenteducational levels which range from no formal education (39.5%) to college and above levels(29.6%).…”
Section: Discussionmentioning
confidence: 99%
“…But those who used it were satisfied. 23 The similar study reported that 72.1% of women were satisfied with Implant and for them it was a long term cost-effective method of contraception. Contrary to this another study conducted by Wong RC, et al making comparison of women using two different forms of long-term reversible contraception showed that there was more dissatisfaction amongst the Implant (60.9%) than the IUD users (17.2%).…”
Section: Discussionmentioning
confidence: 94%
“…The reason is that most of them at this age have at least one to two children and women then want birth spacing. 8,13,18,[21][22][23] Our study results reveal that knowledge of the participants about at least one method was 80% but only 26% of all women had used it. Only seven of these 26% women (i.e; only 21%) had used Implant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation